CITIZENSHIP STATUS AND INHERITANCE OF ADOPTED CHILDREN CARRIED OUT BY SPOUSES OF FOREIGN NATIONALS IN INDONESIA - Meliala, Indriani Putri Sofyanti (International Journal of Research -GRANTHAALAYAH, 2020)
Children are a gift from God Almighty that is dreamed of by every couple. Couples who do not have offspring usually adopt children to continue their lineage and maintain their marriage. Appointment of children in Indonesia is the adoption of children between Indonesian citizens (domestic adoption) and the adoption of children by Foreign Citizens (Intercountry adoption). Requirements and procedures the appointment of an Indonesian citizen by a foreign national is explained in PP No. 54 of 2007 concerning Implementation of Child Appointment, Minister of Social Affairs Regulation No. 110 / HUK / 2009 Regarding the Requirements for Appointment of Children, the two regulations are inseparable from Law No. 35 of 2014 concerning Child Protection. The purpose of this study is to examine and determine the status of inheritance and legal consequences on the citizenship status of the process of adopting Indonesian Citizens’ children by Foreign Citizens after a court ruling. The research method used is a normative juridical approach that is by focusing on data and field interviews to study primary, secondary, tertiary data collected in the form of traditional materials that are related to the problem under study which will then be analyzed in a qualitative juridical manner, then analyzed descriptively analytically to obtain a comprehensive and systematic picture of the problem under investigation connected with applicable legal regulations. The results showed that there were still many Indonesian citizens being adopted by foreign citizens who did not comply with the procedures. Problems that arise are regarding citizenship status and inheritance of adopted children. If the adopted child has a foreign nationality, he/she cannot obtain an estate with ownership status, but can only control the usage rights. This is stated in Article 21 of the Basic Agrarian Law.